A meta-analysis of randomized controlled studies comparing off-pump vs on-pump CABG in the elderly. (14th October 2021) - Machado, R J; Saraiva, F A; Mancio, J; Sousa, P; Cerqueira, R J; Barros, A S; Lourenco, A P; Leite-Moreira, A F
Abstract: Background: The increasing demand for coronary revascularization in the elderly has raised the interest in off-pump coronary artery bypass graft (CABG) as an option in these high-risk patients. Purpose: We sought to investigate the differences between off-pump CABG (OPCAB) and on-pump CABG (ONCAB), among patients older than 60, in short and mid-term results throughout a meta-analysis of randomized clinical trials (RCTs). Methods: A literature search was conducted using MEDLINE, ISI Web of Science and Cochrane Library (1960–2020). RCTs reporting mortality outcomes of OPCAB vs ONCAB within elderly patients (as prespecified or secondary analysis) were included. Data on myocardial infarction, stroke, repeat revascularization, renal failure and composite endpoints after CABG were also collected. Hazard ratio (HR) and variance for follow-up outcomes and frequencies or odds ratio (OR) for early endpoints were collected. Random effect models were used to compute statistical combined measures and 95% confidence intervals (CI). Results: Seven RCTs encompassing a total of 6, 609 patients were included (3, 303 OPCAB and 3, 306 ONCAB, 50% were men). Five trials reported mortality during follow-up (6 months (2 studies) to 5 years). There were no significant differences on mid-term mortality (pooled HR: 1.02, 95% CI: 0.88–1.17, p=0.82) and composite endpoint incidence (4 studies pooled HR: 0.98, 95% CI: 0.88–1.09, p=0.73) between OPCAB and ONCAB. At 30-days, no differences between groups were noted in mortality (5 studies pooled OR: 0.90, 95% CI: 0.62–1.31, p=0.59), early myocardial infarction (5 studies pooled OR: 0.95, 95% CI: 0.60–1.51, p=0.82) and renal complications (3 studies pooled OR: 0.74, 95% CI: 0.50–1.11, p=0.14). The need for early repeat revascularization was significantly higher in OPCAB (2 studies pooled OR: 2.58, 95% CI: 1.16–5.75, p=0.02), with higher percentage of incomplete revascularization among OPCAB in both trials included in this pooled result (34% in OPCAB vs 29% in ONCAB, p<0.01). However, OPCAB showed a tendency for lower risk of early stroke (6 studies pooled OR: 0.70, 95% CI: 0.48–1.03, p=0.07). Conclusions: Pooling data from RCTs in elderly patients showed that OPCAB and ONCAB provide similar mid-term results. However, OPCAB was associated with a higher risk of early repeat revascularization and there was a trend for reduced early stroke risk. Further randomized studies, specifically designed to include elderly patients, are needed to establish the better CABG strategy. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Universidade do Porto/FMUP and FSE-Social European Fund; Fundação para a Ciência e Tecnologia